Upaya Pengembangan Stimulus Motorik Halus Pada Anak Retardasi Mental Kategori Sedang - Mahanani, Srinalesti (Educivilia: Jurnal Pengabdian pada Masyarakat, 2020)
Mental retardation children's abilities need to be stimulated related to motor skills in order to be able to skillfully use hand coordination. Cross stitch is a medium that is currently developed not only as an art but as a fine motor stimulus for children. Community Service Activities are carried out at Putera Asih SLB Students in Kediri City. The activity begins with the provision of health education to teachers then the service team teaches Cross Static students. From 21 students there were 17 people who needed full assistance, and 4 of them were partially assisted. Some students bring tools home to practice with their parents and family. In the final activity of this service, the preparation of tools is assisted by devotees and teachers. At this stage, students who are fully assisted are 15 people and 6 people are partially assisted. Cross stitch activity is one of the activities that can stimulate fine motor development. These activities will be able to flex the fingers, improve the ability of fine motor coordination and increase brain stimulus for students with special needs.